Intersexuality in the porcellanid crab Pisidia longicornis (Crustacea: Decapoda: Anomura: Porcellanidae) - Luciane Augusto de Azevedo Ferreira (Zoologia (Curitiba), 2015)
Intersex specimens of Pisidia longicornis (Linnaeus, 1767) are recorded for the first time and their secondary sexual characters are analyzed. Of 145 specimens of P. longicornis examined in this study, six were identified as intersex individuals. Of these, three presented male secondary sexual characters, well-developed male gonopores and rudimentary female gonopores, whereas the other three had female secondary sexual characters, with female gonopores being more pronounced than the male ones. The present study provides the first record of intersex porcelain crabs.